2004
DOI: 10.1080/00480169.2004.36435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training location and time period on racehorse performance in New Zealand. 2. Multivariable analysis

Abstract: Official race and trial results data provided a valuable resource for epidemiological studies of factors influencing racehorse performance. Results of analyses performed here provided little evidence of any adverse impact of a new training surface at the Matamata Racing Club on indirect measures of racehorse performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Horses in training within the northern region of the North Island were also more likely to race, which may in part be because of clustering of the more successful trainers in this region [16,17]. Starters and number of race meetings were also stratified according to regional or premier tracks within the different racing regions, with more race meetings, at a higher frequency, at premier tracks.…”
Section: Discussionmentioning
confidence: 99%
“…Horses in training within the northern region of the North Island were also more likely to race, which may in part be because of clustering of the more successful trainers in this region [16,17]. Starters and number of race meetings were also stratified according to regional or premier tracks within the different racing regions, with more race meetings, at a higher frequency, at premier tracks.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested the apparent effect of age on injury and mortality may be an effect of first year of racing and not of age, per se [29,30], though teasing these apart may be difficult. In many studies horses first racing, successfully, at 2 years have been shown to enjoy a lifetime advantage [22,[30][31][32][33][34][35][36][37][38][39]. However, this interpretation may be unsound if professional judgement in selecting horses ready to train and mortality amongst unsuccessful 2-year-old horses are not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Starts by stallions were relatively low compared with starts by mares and geldings for all breeds. However, for Qhs the proportion of stallions rose progressively, from a 2006-2011, 6-year mean of 9.3 AE 1.42% to a high of 35.0% in 2015. Over the 13-year study period, Tb stallions were responsible for a mean 11.72 AE 6.80% of annual Tb starts, compared with 43.19 AE 5.95% and 45.07 AE 0.76% for Tb geldings and mares respectively.…”
Section: Registry Integritymentioning
confidence: 94%
“…Despite the widespread anecdotal evidence that a relationship between conformation and performance exists, there is a lack of scientific data and studies on conformation of the racing Thoroughbred. Previous studies on which factors influence performance of a racehorse have concentrated on the cardiovascular system (Young et al 2005) or the effect of training (Perkins et al 2004) and there is only one study reported on the relationship between conformation and performance by comparing 'winners' to 'nonwinners' (Delahunty et al 1991). Performance is difficult to quantify and the performance parameters available do not simply reflect the performance potential of the horse, but are influenced by other factors.…”
Section: Performancementioning
confidence: 99%